The economics of money, banking, and financial markets - Mishkin, Frederic S. (World students series, 2001)
Mishkin provides coverage of and many new insights into the monetary policy process, the operation of the Federal Reserve, the regulation and supervision of the financial system, and the internationalization of financial markets.